2005
DOI: 10.2807/esw.10.48.02847-en
|View full text |Cite
|
Sign up to set email alerts
|

Large outbreak of Salmonella Typhimurium DT104, the Netherlands, September–November 2005

Abstract: At the end of September 2005, an outbreak of Salmonella Typhimurium DT104 infections was detected in the Netherlands. From 19 September to 7 November 2005, 165 extra cases of S. Typhimurium DT104 infection were recorded

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…The result of antimicrobial susceptibility testing in this study revealed that all Salmonella serotypes were 100% resistant to ampicillin, 90.6% to tetracycline, and 71.9% to streptomycin (Table 2). These results were not unusual as increasing resistance of non-typhoidal Salmonella to ampicillin, tetracycline, cotrimoxazole and chloramphenicol have been reported in many parts of the world such as the Netherland (Kivi et al, 2005), Singapore (Ling et al, 2002), Finland (Takkinen et al, Kenya (Kariuki et al, 2006b) and Nigeria (Akinyemi et al, 2007). Drug abuse, over the counter sales of antibiotics, use of antibiotics as growth promoter in animal and prophylaxis use of sulphamethoxazole-pyrimethamine for plasmodiasis were some factors linked to the increasing resistance to these antibiotics (Kariuki et al, 2006b).…”
Section: Discussionmentioning
confidence: 58%
“…The result of antimicrobial susceptibility testing in this study revealed that all Salmonella serotypes were 100% resistant to ampicillin, 90.6% to tetracycline, and 71.9% to streptomycin (Table 2). These results were not unusual as increasing resistance of non-typhoidal Salmonella to ampicillin, tetracycline, cotrimoxazole and chloramphenicol have been reported in many parts of the world such as the Netherland (Kivi et al, 2005), Singapore (Ling et al, 2002), Finland (Takkinen et al, Kenya (Kariuki et al, 2006b) and Nigeria (Akinyemi et al, 2007). Drug abuse, over the counter sales of antibiotics, use of antibiotics as growth promoter in animal and prophylaxis use of sulphamethoxazole-pyrimethamine for plasmodiasis were some factors linked to the increasing resistance to these antibiotics (Kariuki et al, 2006b).…”
Section: Discussionmentioning
confidence: 58%
“…The Netherlands initially responded negatively to the Enter-net inquiry, but some weeks later discovered an outbreak with the same strain of MDR-DT104 [14]. Both outbreaks, the Danish and the Dutch, were notified to the infectious community through brief, early reports in the weekly bulletin Eurosurveillance [15, 16] and the Danish outbreak was also reported in the national weekly epidemiological bulletin [17].…”
Section: Resultsmentioning
confidence: 99%
“…As a final point, infections with SE have decreased substantially in recent years (RIVM, 2013), whereas those with ST mv have emerged quickly and those with ST remained relatively stable during the last decade (RIVM, 2013), with some major outbreaks detected Kivi et al, 2007, Kivi et al, 2005van Duynhoven et al, 2009;Whelan et al, 2010). It is then increasingly important to provide public health surveillance with suitable data targets and analytical tools to differentiate the sources of Salmonella within these serovars.…”
Section: Discussionmentioning
confidence: 96%